2009
DOI: 10.1051/0004-6361/200810715
|View full text |Cite
|
Sign up to set email alerts
|

The Hαgalaxy survey

Abstract: Aims. We analyse the current build-up of stellar mass within the disks and bulges of nearby galaxies through a comparison of the spatial distributions of forming and old stellar populations. Methods. Hα and R-band imaging are used to determine the distributions of young and old stellar populations in 313 S0a-Im field galaxies out to ∼40 Mpc. Concentration indices and mean normalised light profiles are calculated as a function of galaxy type and bar classification.Results. The mean profiles and concentration in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 62 publications
12
78
0
Order By: Relevance
“…To make this point more quantitative, we have estimated the fraction of total SF that might be expected in an unbarred galaxy in the radial range covered by the extracted SFD slit spectra for each of the 4 galaxies studied. This was done using averaged Hα profiles for unbarred galaxies of the same Hubble T -type (Sb or Sa), taken from James, Bretherton, & Knapen (2009). The resulting fractions are: for NGC 2543, 33 per cent; for NGC 2712, 26 per cent; for NGC 3185, 37 per cent; and for NGC 3351, 15 per cent, with the smaller value for the last galaxy being due to its shorter bar.…”
Section: Discussionmentioning
confidence: 99%
“…To make this point more quantitative, we have estimated the fraction of total SF that might be expected in an unbarred galaxy in the radial range covered by the extracted SFD slit spectra for each of the 4 galaxies studied. This was done using averaged Hα profiles for unbarred galaxies of the same Hubble T -type (Sb or Sa), taken from James, Bretherton, & Knapen (2009). The resulting fractions are: for NGC 2543, 33 per cent; for NGC 2712, 26 per cent; for NGC 3185, 37 per cent; and for NGC 3351, 15 per cent, with the smaller value for the last galaxy being due to its shorter bar.…”
Section: Discussionmentioning
confidence: 99%
“…However, these two phenomena are probably unrelated. James et al (2009) studied the radial distribution of Hα emission in a large sample of spiral galaxies and found that the late-type spirals (Sc+) show a Hα flux deficit in the bulge regardless of the presence of bars. This effect is much less pronounced in the Sa-type spirals or even absent in their barred counterparts, which tend to have a high concentration of the Hα emission toward the center.…”
Section: Hα Flux Extinction and Star Formation Ratementioning
confidence: 99%
“…According to James et al (2009), there is a significant difference in the Hα radial profile of barred and unbarred Sb galaxies. The unbarred Sb galaxies show a smooth profile similar to Sa galaxies.…”
Section: Hα Flux Extinction and Star Formation Ratementioning
confidence: 99%
“…Although the general overview of the impact of a bar on a galactic disc is well accepted, the details of the process, and its dependence on galactic properties, pose many remaining questions. While the presence of a bar often causes an increase of the SFR, several observations show no increase (Pompea & Rieke 1990;Martinet & Friedli 1997;Chapelon et al 1999) or an increase only in early-type spiral galaxies (Ho et al 1997;James et al 2009). Recent work with the volunteer-based identification of morphological types by the Galaxy Zoo team showed that the specific star formation rate (SSFR) is anti-correlated with the presence of a bar (Cheung et al 2013) but at same time the relation between the SFR and the stellar mass M * seems unaffected by the presence of a bar (Willett et al 2015).…”
Section: Introductionmentioning
confidence: 99%